Phenotypic selection in Lepanthes rupestris Stimson - Cintrón Berdecía, Sol Taína (Universidad de Costa Rica, 2016)
Natural selection is defined as a process in which a population has: variation among individuals, a strong relationship between a character and repro- ductive success (fitness differences) and character heritability (Endler 1986).